Association between risk factors of non-alcoholic fatty liver with the sonographic findings among adults at Golden Horses Health Sanctuary, Selangor, Malaysia - Khammas, Abdul Sattar Arif (2017)
NAFLD is the most common type of hepatic steatosis, developing through three main stages, from simple hepatic steatosis to non alcoholic steatohepatitis (NASH), that leads to fibrosis and cirrhosis with the end-stage of HCC. It is strongly associated with metabolic syndrome, such as dyslipidemia, T2DM, hypertension and obesity. Therefore, NAFLD is considered an independent risk factor for the development of cardiovascular disease (CVD). The present study was proposed to determine the contributing factors to NAFLD amongst Malaysian adults in the Klang Valley as well as the association between these factors and grading of NAFLD. This study was also designed to assess the differences of hepatic echo-intensity attenuation rate and subcutaneous tissue thickness between NAFLD patients and non-NAFLD subjects.